Catalyst-free synthesis of α-thioacrylic acids via cascade thiolation and 1, 4-aryl migration of aryl alkynoates at room temperature. Issue 37 (13th September 2018) - Wei, Wei; Wang, Leilei; Yue, Huilan; Jiang, Yuan-Ye; Yang, Daoshan
Abstract : A simple and facile catalyst-free strategy has been developed for the synthesis of α-thioacrylic acids from readily-available aryl alkynoates and thiols at room temperature under air. Abstract : A simple and facile catalyst-free method for the construction of α-thioacrylic acids has been developed from readily-available aryl alkynoates and thiols at room temperature. Various α-thioacrylic acids could be conveniently and efficiently obtained in moderate to good yields via cascade thiolation and 1, 4-aryl migration of aryl alkynoates in the absence of any catalyst and additive.